Studi Kasus Preferensi Kepemimpinan Alumni LATSAR CPNS Tahun 2025 di Wilayah Kerja BDK Denpasar - Ninik Uswatun Fadilah; I Wayan Lasmawan; Desak Putu Parmiti (LPPM Institut Pendidikan Nusantara Global, 2026)
This study examines the preferences for effective leadership among prospective civil servants who participated in the 2025 Pre-Service Training (Latsar CPNS) at the Balai Diklat Keagamaan Denpasar. Strengthening leadership competence is essential for building a professional and adaptive state apparatus, particularly among Generation Z employees who are entering government institutions during the era of rapid digital transformation. The purpose of this research is to identify how participants perceive effective leadership across five key indicators: leadership character, leader attitudes, positive leadership behaviors, negative leadership tendencies, and leadership competencies relevant to Society 5.0. This study employs a mixed-method case study design using multiple-choice questions and open-ended responses. Quantitative data were analyzed descriptively, while qualitative data were examined using the Miles and Huberman interactive model (data reduction, data display, and conclusion drawing). The findings reveal that participants prefer leaders who are democratic, open, communicative, supportive, and technologically competent. Positive leadership practices are highly valued, while negative leadership behaviors such as intimidation and resistance to innovation are strongly rejected. The study concludes that effective leadership for Generation Z requires a combination of ethical character, participatory attitudes, digital competence, and the ability to empower subordinates. Recommendations emphasize the urgency of leadership development programs aligned with the demands of Society 5.0.